Improvement in vitro Dissolution Rate of Quercetin Using Cocrystallization of Quercetin-Malonic Acid - Dwi Setyawan; Sukma Adhi Permata; Ahmad Zainul; Maria Lucia Ardhani Dwi Lestari (Indonesian Journal of Chemistry, 2018)
The aim of the study was to improve the in-vitro dissolution rate of quercetin (Qu) using cocrystallization of quercetin. Cocrystals of quercetin (Co Qu) were produced with malonic acid (Ma) as coformer at ratio 1:2 using solvent evaporation method. Cocrystals quercetin-malonic acid (Co Qu-Ma) was characterized using Differential Thermal Analysis (DTA), Powder X-Ray Diffraction (PXRD), Scanning Electron Microscope (SEM), and Fourier Transforms Infrared Spectrophotometer (FTIR) and in-vitro dissolution study. A new endothermic peak at 277.9 °C was shown from the thermogram. Diffractogram of Co Qu-Ma showed a new diffraction peak at 2θ 9.81, 12.99, and 19.80°. Microphotograph showed that Qu and Ma exhibited a columnar-shaped and a pebble-shaped crystal, respectively, and FTIR wavenumber of O-H functional group of quercetin was shifted from its original position at 3411 to 3428 cm-1 in the physical mixture (pm) of Qu-Ma and 3418 cm-1 in Co Qu-Ma, respectively. The physicochemical characterizations using DTA, PXRD, SEM and FTIR indicated that Co Qu-Ma were successfully obtained through solvent evaporation method. The in-vitro dissolution rate of Co Qu-Ma was 95.30% at 60 min. Cocrystals effectively increased dissolution rate and dissolution efficiency in comparison to the pure quercetin and physical mixture of quercetin-malonic acid.